Research progress of functional motifs based on growth factors in cartilage tissue engineering: A review - Qin, Shengao; Zhu, Jiaman; Zhang, Guangyong; Sui, Qijia; Niu, Yimeng; Ye, Weilong; Ma, Guowu; Liu, Huiying (Frontiers in Bioengineering and Biotechnology, 2023)
Osteoarthritis is a chronic degenerative joint disease that exerts significant impacts on personal life quality, and cartilage tissue engineering is a practical treatment in clinical. The three elements of cartilage tissue engineering are seed cells that initiate tissue reconstruction, biological scaffolds that provide support and guidance, and growth factors that induce chondrogenic differentiation of seed cells and cartilage matrix secretion. Various growth factors are involved in cartilage regeneration and play important roles therein, which is the focus of current cartilage repair strategy. To compensate for the purification difficulty, high cost, poor metabolic stability, and circulating dilution of natural growth factors, the concept of functional motifs (also known as mimetic peptides) from original factor was introduced in recent studies. Here, we reviewed the selection mechanisms, biological functions, scaffold carriers, and modification methods of growth factor-related functional motifs, and evaluated the repair performance in cartilage tissue engineering. Finally, the prospects of functional motifs in researches and clinical application of osteoarthritis were discussed.